Gene expression signatures of mutualism and pathogenesis in flax roots - Quintans, Isadora Louise Alves da Costa Ribeiro; Vukicevich, Eric; Kokkoris, Vasilis; Packard, Erica; Adhikary, Dinesh; Hart, Miranda M.; Deyholos, Michael K. (Frontiers in Plant Science, 2024)
Fusarium wilt, a devastating soil-borne fungal disease in flax (Linum usitatissimum), is caused by Fusarium oxysporum f. sp. lini, a hemibiotrophic plant pathogen that penetrates plant roots. There are several reports of the molecular response of L. usitatissimum to F. oxysporum f. sp. lini; however, comparisons of the effects of mutualistic and pathogenic fungi on plants are more limited. In this study, we have integrated phenotyping and RNA-Seq approaches to examine the response of flax to F. oxysporum f.sp. lini and to a mutualistic arbuscular mycorrhizal fungus (AMF), Rhizoglomus irregulare. R. irregulare is a common soil fungus and also widely used as a commercial inoculant to improve plant growth. We measured flax growth parameters after plant inoculation with one or both fungi, in comparison with a non-inoculated control. We performed transcriptome analysis of root tissues collected at 9 and 14 days post-inoculation. We identified several differentially expressed genes (DEGs) in response to pathogenic and mutualistic fungi. These included genes related to ethylene and salicylic acid biosynthesis, carbohydrate binding, oxidoreductases, and sugar transmembrane transporters. Genes related to calcium signaling, nutrient transport, lipid metabolism, cell wall, and polysaccharide-modification were up-regulated by R. irregulare; however, the same genes were downregulated by F. oxysporum f. sp. lini. In the combined treatment, several genes related to cell wall modifications, hormone regulation and nutrient uptake were up-regulated. These results suggest that inoculation with R. irregulare reduced gene expression related to F. oxysporum f. sp. lini infection, leading to a reduced response to the pathogen. In response to AMF, flax prioritized mutualism-related gene expression over defense, reversing the growth inhibition caused when F. oxysporum f. sp. lini was inoculated alone. This research provides insights into the protective effects of AMF, revealing the pre-symbiotic gene expression profile of flax in response to a mutualist in comparison with a pathogen.Potential target genes for crop improvement were identified, especially defense-related genes.